<span>The correct answer is 2x</span>²<span>-16x+30.
Explanation<span>:
(p*q)(x) is a composition of the two functions p(x) and q(x); it is the same as p(q(x)). We replace every x in p(x) with our value of q(x), x-3:
instead of 2x</span></span>²<span><span>, we have 2(x-3)</span></span>²<span><span>, and instead of -4x, we have -4(x-3).
This gives us 2(x-3)</span></span>²<span><span>-4(x-3). This is the same as 2(x-3)(x-3)-4(x-3).
Multiplying, we have
2(x*x-3*x-3*x-3(-3))-(4*x-4*3)
=2(x</span></span>²<span><span>-3x-3x+9)-(4x-12)
=2(x</span></span>²<span><span>-6x+9)-4x+12.
Using the distributive property gives us
2*x</span></span>²<span><span>-2*6x+2*9-4x+12
=2x</span></span>²<span><span>-12x+19-4x+12.
Combine like terms, and we have 2x</span></span>²<span><span>-16x+30.</span></span>
Answer:
m∠A = 15°; m∠B = 89°; m∠C = 76°
Step-by-step explanation:
The sum of the three interior angles of a triangle is 180°.
Let x = m∠A
Then 3x + 44 = m∠B
and x + 61 = m∠C
x + 3x + 44 + x + 61 = 180
5x + 105 = 180
5x = 75
x = 15
m∠A = 15°
m∠B = 3(15) + 44 = 45 + 44 = 89°
m∠C = 15 + 61 = <u> 76°</u>
Sum = 180°
It is exponentially each time you are dividing by 4/3
Answer:
explain further or send a picture of what you mean and then I can help you
Answer:
858 the next one is 947
Step-by-step explanation:
I hope it's right bye